2001
DOI: 10.1139/t00-081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cementation on the small-strain parameters of sands

Abstract: Natural cementation affects the properties of soils, the interpretation of in situ and laboratory test results, and the selection of criteria for geotechnical design. In this paper, published experimental studies are reviewed, a microscale analysis is presented of the effect of cementation on small-strain stiffness for distinct stress-cementation histories, and the effect of cementation on small-strain velocity and damping is experimentally studied. Observations include the prevailing effects of cementation ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(46 citation statements)
references
References 22 publications
3
38
1
4
Order By: Relevance
“…Further studies indicated that no liquefaction or lateral flow occurred in the foundation soils [9]. The measurements of dynamic properties of cemented soil by tests including cyclic triaxial, resonant column, and wave propagation methods, as reported by Saxena et al [51,52], Fernandez and Santamarina [22], and Khan et al [35]. The results demonstrated that artificial cementation of hazardous sandy soil can significantly mitigate the seismic-induced damage.…”
Section: Cementation Of Soilmentioning
confidence: 90%
“…Further studies indicated that no liquefaction or lateral flow occurred in the foundation soils [9]. The measurements of dynamic properties of cemented soil by tests including cyclic triaxial, resonant column, and wave propagation methods, as reported by Saxena et al [51,52], Fernandez and Santamarina [22], and Khan et al [35]. The results demonstrated that artificial cementation of hazardous sandy soil can significantly mitigate the seismic-induced damage.…”
Section: Cementation Of Soilmentioning
confidence: 90%
“…The longevity of steel structures and concrete elements underground will be reduced in the alkaline environment (Mitchell and Soga, 1976;Perry, 1977;Sherwood, 1993). Moreover, traditionally treated soils also exhibit an excessive brittle performance especially under traffic loading or impact loading (Fernandez and Santamarina, 2001;Okyay and Dias, 2010). To overcome these problems, a new alternative soil stabilizer that improves soils environmentally friendly and maintains sufficiently ductile treated soils must be found.…”
Section: Introductionmentioning
confidence: 99%
“…Trends clearly show the transition from stress-controlled to hydrate-controlled stiffness in hydrate-bearing sediments. We fit the data using a theoretical expression initially developed for cemented soils (Fernandez and Santamarina, 2001):…”
Section: Analysis and Discussionmentioning
confidence: 99%